Effects of Combination Therapy of Escitalopram with Magnesium Oxide versus Escitalopram Alone in Major Depressive Disorder - Jahan, Mst Wahida; Ara, Shahin; Alim, Mostofa; Saikat, Md Rakibuzzaman Chowdhury; Rahman, Md Matiur; Moni, Sabiha Yasmin; Haque, Lotifa; Haque, Nazmul (KYAMC Journal, 2025)
Background: Major depressive disorder (MDD) is one of the most common mental illnesses and a leading cause of disability worldwide. Medications and psychotherapy together act well for remission of MDD. The aim of the study was to determine the efficacy of Escitalopram with MgO versus Escitalopram alone in the treatment of major depressive disorder. Materials and Methods: This randomized clinical trial on major depressive disorder was conducted in the Department of Pharmacology and Therapeutics in collaboration with the outpatient department of Psychiatry, Rajshahi Medical College Hospital, Rajshahi for a period of 1 year from July 2022 to June 2023. Based on predefined eligibility criteria, a total number of 90 patients with major depressive disorder were included in this study. The study population was divided into two groups. In Group-A (study group) 45 patients were treated with Escitalopram (10 mg/day) with MgO (365 mg/day) and in Group-B (control group) 45 patients were treated with Escitalopram (10 mg/day) alone for 12 weeks. Results: The mean ages of the patients were 26.31 ± 7.85 years and 24.98 ± 5.38 years in the study group and control group, respectively. Reduction of BDI-II (BV) test score from baseline to the end of 12 weeks of drug administration between the two groups was found statistically highly significant (p < 0.001). The mean percent of reduction of BDI-II (BV) test scores were 89.39±9.41 and 62.43±9.98 in study group and control group, respectively and it was also statistically highly significant (p < 0.001). On the basis of achievement of BDI-II (BV) test score ≤ 13, Escitalopram with MgO was more effective than Escitalopram alone in major depressive disorder and it was statistically highly significant (p < 0.01). Conclusions: So, The combination of Escitalopram with Magnesium oxide (MgO) is more beneficial in MDD than Escitalopram alone. KYAMC Journal Vol. 15, No. 04, January 2025: 178-183